Nitrate toxicity in forage crops: Causes and remedial measures - Prasanna, S P; Manjunath, Manjunath; Kumar, S K Dinesh; Kumar, Rakesh (Indian Farming, 2020)
Dairy cattle work with the principle of converting forage crops which are useless for man into a useful product such as milk, curd, ghee and other milk products. Forage crops especially cereal forage have problem of nitrate toxicity when excess amount of fertilizer is applied to the crop. Forage crops can accumulate higher amounts of nitrate (NO3). High amount of nitrates can accumulate in cereal grains (oats, rye, wheat, barley, triticale, etc.), sorghum, sudan grass, millet, corn and on very rare occasions, alfalfa. There are several reasons behind the accumulation of higher amounts of nitrates in the crops, especially under the adverse environmental conditions. Abnormal growing conditions such as drought, frost, unseasonable or prolonged cool temperatures, hail, shade, disease and herbicide damage can cause high nitrate accumulation in forage.